Transfusion-dependent pure red cell aplasia secondary to antierythropoietin antibodies successfully treated with renal transplantation. (29th September 2015) - Demetriou, A; Ledermann, SE; Sebire, NJ; Ancliff, P; Macdougall, I; Casadevall, N; Marks, SD
Abstract : Aims: Pure red cell aplasia (PRCA) is an isolated arrest of erythropoiesis which has been reported to occur in patients with chronic kidney disease (CKD) secondary to the development of antibodies against erythropoiesis-stimulating agents, usually erythropoietin α. Methods: To report the successful outcome of pre-emptive living related renal transplantation in a 6.5-year-old boy with CKD due to renal dysplasia who developed antierythropoietin antibodies (anti-epo Abs) resulting in transfusion-dependent PRCA. He developed a papular skin rash with lesions on his arms and legs nine months prior to his renal transplantation which was confirmed on skin biopsy as acute panniculitis. Results: He was noted to have anaemia requiring increasing doses of subcutaneous erythropoietin β up to 465 Units/kg/week for two years. Two months prior to transplantation, his haemoglobin was 4.6 g/dl with a low reticulocyte count of 2×10 9 /l (0.1%) requiring his first blood transfusion of washed cells. His bone marrow aspirate and trephine biopsy one month before renal transplantation confirmed PRCA. There was no evidence of malignancy, haemolysis, haemorrhage, viral infection or auto-immune disease. His erythropoietin β was discontinued and he had high titres of anti epo Abs of 63U/ml (limit of positivity of 0.1 U/ml). He received his second blood transfusion before his renal transplant when his haemoglobin was 6.7 g/dl. He underwent a living related renal transplantation from his maternal uncle (mismatch 0, 1, 1) using triple immunosuppression (azathioprine and tacrolimus from one and two weeks prior to transplantation, respectively, with corticosteroids). His anti-epo Abs reduced further from 13 to 6.5 U/ml 2 weeks post-transplantation but his haemoglobin had fallen to 5.9 g/dl when he required his third and final blood transfusion. Currently, he is three months post-transplant and has been maintaining a stable haemoglobin of between 9.7 and 11.0g/dl, with ferritin of 605 mcg/l (not on iron or folate supplementation), reticulocyte count of 84–130×10 9 /l (2–4%) with declining anti-epo Abs of 2.4U/ml. He has good renal allograft function with plasma creatinine of 52 μmol/l giving an estimated glomerular filtration rate of 75 ml/min/1.73 m 2 . Conclusion: This is the first reported paediatric case where renal transplantation has successfully treated transfusion-dependent PRCA secondary to neutralising anti-epo Abs against erythropoietin β.